First-Principles Calculation on Initial Stage of Oxidation of Si (110)-(1 × 1) Surface - Takahiro Nagasawa; Koji Sueoka (Advances in Condensed Matter Physics)
The initial stage of oxidation of an Si (110)-(1 × 1) surface was analyzed by using the first-principles calculation. Two calculation cells with different surface areas were prepared. In these cells, O atoms were located at the Si–Si bonds in the first layer (A-bonds) and at the Si–Si bonds between the first and second layers (B-bonds). We found that (i) the most stable site of one O atom was the A-bond, and (ii) an O (A-bond) –Si–O (A-bond) was the most stable for two O atoms with a coverage ratio of 𝑅ox=0.06 while an O (A-bond) –Si–O (B-bond) was the most stable for 𝑅ox=0.10. The stability of O (A-bond) –Si–Si–O (A-bond) was less than the structures obtained in (ii). The other calculations showed that the unoxidized A-bonds should be left when a coverage ratio of 𝑅ox is close to 1. These simulations suggest that the O atoms will form clusters in the initial stage of oxidation, and the preferential oxidation will change from the A-bonds to the B-bonds up to the formation of 1 monolayer (ML) oxide. The results obtained here support the reported experimental results.